Investigation of the Bearing Capacity of Foundations on Encased Stone Columns Using Finite Element Method - Kardgar, Hassan (International Journal of Integrated Engineering, 2018)
Soft cohesive soils containing much silt or clay content with low bearing capacity are not suitable for deep vibratory compaction. In order to improve the bearing behavior of these types of soils to withstand against heavy building loads, the surrounding soil mass must be reinforced with any stiff physical or chemical admixture. Using stone column technique has been proven to be one of the most appropriate methods of improving soil strength. By employing vertical columns of compacted aggregate through the soils, vertical load carrying capacity and shear resistance in the soil mass will be improved. However, the effect of various parameters on the amount of this enhancement is not fully identified. To that end, the geotechnical finite element program PLAXIS was employed to model the effect of stone column application on the bearing capacity of clay soils. According to the results, as important factors, the influence of the length of the stone columns and the stiffness of their encasement is more significant and need to be considered in the comprehensive analysis and design of the soil-structure system.